2002
DOI: 10.1210/jc.2001-011940
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Tolerance, Insulin Sensitivity, and Insulin Secretion in Children Born Small for Gestational Age

Abstract: Intrauterine growth retardation is associated with an increased risk of developing adult diseases, such as noninsulin-dependent diabetes mellitus (NIDDM). NIDDM could result from a decreased insulin sensitivity or a reduced insulin secretion or a combination of both. Glucose tolerance, insulin sensitivity, and insulin secretion were studied in prepubertal children born small for gestational age (SGA). Twenty-nine SGA children with a mean age of 9.1 +/- 1.1 yr and 24 children born appropriate for gestational ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
153
3
14

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 234 publications
(180 citation statements)
references
References 30 publications
10
153
3
14
Order By: Relevance
“…Previous studies show that school-aged SGA born children have reduced insulin sensitivity and higher blood pressure than AGA born controls (2,3,6,8,9). Reduced insulin sensitivity in SGA born infants can already be demonstrated in early childhood (5,7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies show that school-aged SGA born children have reduced insulin sensitivity and higher blood pressure than AGA born controls (2,3,6,8,9). Reduced insulin sensitivity in SGA born infants can already be demonstrated in early childhood (5,7).…”
Section: Discussionmentioning
confidence: 99%
“…This is based on the studies of Barker et al (1), who first indicated the importance of fetal growth for development of the metabolic syndrome in adulthood and showed an increasing prevalence with decreasing birth weight. Not only term smallfor-gestational-age (SGA) born infants, but also preterm born infants have an increased prevalence of several components of the metabolic syndrome, already in childhood (2)(3)(4)(5)(6)(7)(8)(9). The relation between metabolic syndrome components in childhood and fetal growth was studied by Jaddoe et al (10); they showed that first trimester fetal growth restriction is associated with an adverse cardiovascular risk profile at 6 y of age.…”
mentioning
confidence: 99%
“…A recent study shows that insulin sensitivity was not affected in prepubertal children born SGA with subsequent catch-up growth provided that they showed a current BMI within the normal range [25]. Here, we showed that catch-up height has no influence on insulin resistance in subjects born SGA, which is in agreement with studies reporting that insulin resistance is not related to linear growth in children born SGA [25,26]. By contrast, we found a strong effect of catch-up in BMI on insulin resistance in subjects born SGA.…”
Section: Bmi (Sds)mentioning
confidence: 99%
“…La falta de asociación entre SM y la condición de desnutrición neonatal establecida por las tablas de Juez y Pittaluga/ Alarcón se podría atribuir a que el percentil 10 de IPN no sea el mejor valor de corte para predecir El resultado más sorprendente de nuestro estudio fue la reducción en el riesgo de SM observada en escolares obesos que tuvieron IPN > 90, hallazgo que contrasta con la menor sensibilidad a la insulina descrita para este grupo de RN cuando fueron clasificados en base al peso de nacimiento [27][28][29] . Adicionalmente, las curvas obtenidas al graficar la relación entre el logaritmo del riesgo de SM y el estado nutricional neonatal fueron diferentes si éste fue descrito por IPN o por el peso de nacimiento corregidos por edad gestacional.…”
Section: Discussionunclassified
“…La función que asocia el peso de nacimiento y la glicemia post carga en escolares asume forma de U, teniendo los niños que fueron pequeños y grandes para la edad gestacional menor sensibilidad a la insulina que sus controles normales [27][28][29] . Sin embargo, al evaluar el riesgo de síndrome metabólico infanto-juvenil de acuerdo al estado nutricional neonatal, los resultados han sido contrapuestos 30,31 .…”
unclassified